Analisis Analisis Moral Sopan Santun Siswa Kelas V Sekolah Dasar Negeri 001 Koto Peraku Kecamatan Cerenti Kabupaten Kuantan Singingi: Analisis Moral Sopan Santun Siswa Kelas V Sekolah Dasar - Tria tria; Hendri Marhadi; Guslinda (STKIP Subang, 2025)
This research is based on the phenomenon of the fading of moral values of manners in the elementary school student environment, such as reduced respect for teachers and the negative influence of technological developments. Based on Lawrence Kohlberg's theory of moral development, this study aims to describe the moral behavior of class V students and the factors that influence them. The method used was qualitative descriptive with the subject of teacher of class V and grade V students of SD Negeri 001 Koto Peraku. Data were collected through observation, interviews, documentation, and assessment rubrics, then analyzed using the Miles and Huberman model. The observation results showed that students generally showed polite behavior, such as respecting the teacher and interacting politely. However, some students still lack self-control and speak politely. Meanwhile, the results of the interviews reinforce that the influence of digital media is a factor causing the decline in manners. Meanwhile, the results of the assessment rubric showed an average score of 82.6% with the Good category. This study concludes that the formation of students' moral manners is influenced by internal factors (habits and personality) as well as external factors (family, school environment, digital media). Keywords: Moral manners, elementary school students, character education, moral formation factors.